Confirmatory Factor Analysis (CFA) Interaksi Dosen-Mahasiswa dalam Pembelajaran Daring - Nurul Izzah Mardhotillah; Yulhendri Yulhendri (Jurnal Salingka Nagari, 2022)
Abstract: The interaction of students and lecturers in the classroom has changed to online. However, the influence of lecturer-student interactions in online learning, particularly in the participation of lecturers and students in online learning get many concerns. In addition, efforts are made to preserve the social bond between professors and students. While these interactions are necessary for learning, they do not directly benefit students'understanding and aptitude. Cognitive contact requires effort in learning, which starts with establishing a space for discussion and providing feedback as soon as possible. This type of research is descriptive quantitative. With 358 respondents, the sample was taken using the Slovin formula. The data used in this study is primary data obtained from students of the Faculty of Economics, Universitas Negeri Padang through questionnaires. Confirmatory factor analysis (CFA) with SmartPLS 3.0 was used for analysis. The findings of this study indicate that the interaction between lecturers and students has a major effect on students.